Analysis of the causal relationship between agricultural imports and some economic variables in Iraq - العبدلي سعد; كاطع اسراء سليم (Journal of Economics and Administrative Sciences, 2015)
Foreign trade receives a good deal of economists’ attention for its active contribution to economic growth, and imports of goods and services that could not be produced locally constitute an important share of the local economy. Agricultural imports constitute an important share of the total imports due to their role in fulfilling the needs of local markets; however, the agricultural sector in Iraq contributes no more than a limited share of the country’s need, which has encouraged the import of a variety of fruits, vegetables and strategic crops and different types of red and white meat. For the sake of identifying the factors affecting the demand on agricultural imports in Iraq, the following factors has been analyzed: the causal (Granger) relationship among the amount of agricultural imports (IM), the variable of gross domestic product (GDP), prices of agricultural import (PI), and foreign reserve (TR). The results indicate that a higher proportion of the contribution of the agricultural imports were in 1995 amounted to 37% and agricultural imports are going increasingly with rising GDP and this reflects the positive relationship between income and demand, and pointed to the existence of a deficit in agricultural trade balance as agricultural imports has exceeded Agricultural exports during the period 1990-2010. The results also showed the existence of a causal relationship going from GDP to the required amount of agricultural imports, as well as the existence of a causal relationship vector of agricultural imports into foreign reserves, and this indicates the possibility of the existence of a complementary relationship shared between them and thus the existence of a long-run equilibrium relationship